2018
DOI: 10.1590/1808-1657000552016
|View full text |Cite
|
Sign up to set email alerts
|

Small ruminant lentiviruses: economic and productive losses, consequences of the disease

Abstract: Small ruminant lentiviruses, caprine arthritis encephalitis virus, and Maedi-Visna virus cause diseases that result in significant productive losses, mostly in dairy animals. These viruses belong to the Retroviridae family, Lentivirus genus, and constitute a heterogeneous group, which may generate implications for the diagnosis and control of small ruminant lentiviruses. Losses caused by them are associated with reproductive failure, short productive life, and decreased milk production by the infected animals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 56 publications
0
9
0
7
Order By: Relevance
“…A artrite encefalite caprina (CAE) e a maedivisna (MV) são doenças infectocontagiosas causadas pelos LVPRs, retrovírus não oncogênicos, responsáveis por acarretar perdas produtivas e reprodutivas, e consequentemente econômicas [10]. Estruturalmente os lentivírus apresentam uma forma esférica, medindo de 80 a 100 nm envelopado por uma bicamada de lipídeos (envelope), a qual surge da membrana celular da célula hospedeira [66].…”
Section: Características Gerais E Resposta Imunológicaunclassified
See 1 more Smart Citation
“…A artrite encefalite caprina (CAE) e a maedivisna (MV) são doenças infectocontagiosas causadas pelos LVPRs, retrovírus não oncogênicos, responsáveis por acarretar perdas produtivas e reprodutivas, e consequentemente econômicas [10]. Estruturalmente os lentivírus apresentam uma forma esférica, medindo de 80 a 100 nm envelopado por uma bicamada de lipídeos (envelope), a qual surge da membrana celular da célula hospedeira [66].…”
Section: Características Gerais E Resposta Imunológicaunclassified
“…O uso dessa técnica no imunodiagnóstico de LVPRs surgiu a partir do momento em que se constatou a carência por um teste que permitisse um resultado mais preciso, aliando altos índices de sensibilidade e especificidade. Associado a isso, a eficácia que o mesmo apresenta frente a outros testes sorológicos, permite otimizar e realizar estratégias de controle, visando reduzir os impactos produtivos, reprodutivos e econômicos que são ocasionadas com o estabelecimento desses agentes virais em um rebanho [10].…”
Section: Lentivírus De Pequenos Ruminantesunclassified
“…Goat and sheep production are associated with traditional systems of subsistence and with economic factors, where animal production tends to be more intensive and demands more efficient production systems (GUILHERME et al, 2017). However, health management with late diagnoses of diverse diseases of different etiologies drastically interferes in the performance of these activities (AZEVEDO et al, 2017). Among the most relevant health problems are the infections caused by small ruminant lentiviruses (SRLVs).…”
Section: General Characteristics Of Small Ruminant Lenvirus Infectionsmentioning
confidence: 99%
“…These diseases cause considerable losses in goat and sheep productions, which may compromise the profitability of the animal farm (AZEVEDO et al, 2017). In addition, the main clinical signs of both infections include arthritis, encephalitis, mastitis and, less frequently, respiratory conditions.…”
Section: General Characteristics Of Small Ruminant Lenvirus Infectionsmentioning
confidence: 99%
“…After the first record of the disease, by Moojen, Soares, Ravazzolo, Pizzol and Gomes (1986) in the state of Rio Grande do Sul, studies have been carried out and shown that the virus has been spreading in Brazil with frequencies that vary according to the type of exploitation, rearing system and breeds used: São Paulo = 15.1% (30/199) (Lara et al, 2013) to 34.9% (96/275) (Madureira & Gomes, 2007); Minas Gerais = 49.5% (531/1072) (Nascimento-Penido, Penido, Galinari, Heinemanns, & Leite, 2017); Rio de Janeiro = 14.1% (79/562) (Cortez-Moreira, Oelemann, & Lilenbaum, 2005); Sergipe = 5.03% (34/675) (Rizzo et al, 2018); Bahia = 0.29% (2/693) (Lima et al, 2013a); Ceará = 40.73% (101/248) (Melo & Franke, 1997); Pernambuco = 18.01% (76/422) (Silva et al, 2012). Pinheiro, Ximenes, Andrioli and Texeira (2009), Lima et al (2013b) and Azevedo et al (2017) identified a total of 73 serological surveys carried out in Brazil. Some studies have shown the economic losses associated with the disease and its risk factors (Alves et al, 2017;Rizzo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%